Timoleague Franciscan Friary, south nave arcade, capital - O'Donovan, Danielle (My University, 2008)
The only moulded capital of the nave arcade (furthest east). Moulding from top down comprises: abacus, quadrant, bell.
Nave arcade
Keywords: quadrant; Architecture, Gothic -- Ireland; Cork (Ireland)--Buildings, structures, etc.; Architecture, Franciscan; Gothic capitals (Architecture); Late Medieval; roll moldings; moldings, hollow